Spectrum of AIDS Defining Opportunistic Infections in a Series of 77 Hospitalised HIV-infected Omani Patients - Balkhair, Abdullah A. (Sultan Qaboos University Medical Journal, College of Medicine & Health Sciences, 2012)
OBJECTIVES: Most of the morbidity and mortality in human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS) result from opportunistic infections (OIs). Although the spectrum of OIs in HIV infected patients from developing countries has been reported, there is a paucity of data on the natural history, pattern of disease, and survival of hospitalised patients with HIV/AIDS, particularly in Arab countries. The aim of this study was to study retrospectively the spectrum and frequency of various OIs in a cohort of hospitalised HIV-infected Omani patients. METHODS: Included in the study were 77 HIV-infected Omani patients admitted to a tertiary care teaching hospital in Muscat, Oman, between January 1999 and December 2008. They were diagnosed on their first admission and hence were not on highly active antiretroviral therapy (HAART) at presentation. The frequency of various clinical and laboratory findings and individual OIs were analysed. RESULTS: In total, 45 patients (58%) had one or more AIDS-defining OIs. Pneumocystis jiroveci pneumonia (PCP) was commonest (25%), followed by cryptococcal meningitis (22%), cytomegalovirus (CMV), retinitis (17%), disseminated tuberculosis (15%), and cerebral toxoplasmosis (12.5%). Only one patient with Mycobacterium avium-intracellulare (MAI) was identified and one patient had disseminated visceral leishmaniasis. The majority of patients (77%) had CD4+ counts <200 cells/μL. Ten patients (22%) died during hospital stays, with five deaths (50%) being caused by disseminated CMV infection. CONCLUSION: A wide spectrum of OIs is seen in hospitalised HIV-infected patients in Oman. P. jiroveci pneumonia and cryptococcal meningitis were the commonest OIs, while disseminated CMV was the commonest cause of death. We hope these results will advance the knowledge of specialists treating HIV in Oman and the Gulf region.